Characteristics of Kampong Chicken (Gallus domesticus) Eggs Based on Shank Color - La Ode Abdul Karim Ishak; Takdir Saili; Muh. Rusdin (Pascasarjana Universitas Sulawesi Tenggara, 2023)
Kampong chickens have genetic characteristics that are not uniform, one of which is the color of the shank. This study aims to analyze the characteristics of Kampong chicken eggs based on the color of the parent shank. The number of eggs observed was 150, consisting of 50 eggs from black shank hens, 50 from white shank hens, and 50 from yellow shank hens. The variables observed in this study were egg color, egg texture, egg weight, and egg index. Egg color and texture were analyzed descriptively based on percentage values. In contrast, egg weight and index were analyzed using analysis of variance in a completely randomized design with 3 treatments and 10 replications. The results of this study indicate that the color of Kampong chicken egg shells in black, white, and yellow shank chickens shows a variety of egg colors. The texture of the Kampong chicken eggshell, based on the color of the shank on the exterior, is quite high quality. The egg weight of black shank-colored Kampong chickens was not significantly different (P>0.05) from that of white and shank-colored chickens. The index of native chicken eggs with yellow shank (P3) was significantly higher (P